Magnetic Interactions and Reversal Mechanisms in Co Nanowire and Nanotube Arrays - Escrig-Murua, J (2013)
Ordered hexagonal arrays of Co nanowires (NWs) and nanotubes (NTs), with diameters between 40 and 65 nm, were prepared by potentiostatic electrodeposition into suitably modified nanoporous alumina templates. The geometrical parameters of the NW/NT arrays were tuned by the pore etching process and deposition conditions. The magnetic interactions between NWs/NTs with different diameters were studied using first-order reversal curves (FORCs). From a quantitative analysis of the FORC measurements, we are able to obtain the profiles of the magnetic interactions and the coercive field distributions. In both NW and NT arrays, the magnetic interactions were found to increase with the diameter of the NWs/NTs, exhibiting higher values for NW arrays. A comparative study of the magnetization reversal processes was also performed by analyzing the angular dependence of the coercivity and correlating the experimental data with theoretical calculations based on a simple analytical model. The magnetization in the NW arrays is found to reverse by the nucleation and propagation of a transverse-like domain wall; on the other hand, for the NT arrays a non-monotonic behavior occurs above a diameter of ? 50 nm, revealing a transition between the vortex and transverse reversal modes. © 2013 American Institute of Physics.